Integrating spectrophotometric and XRD analyses in the investigation of burned dental remains. (May 2020) - Rahmat, Rabiah A.; Humphries, Melissa A.; Austin, Jeremy J.; Linacre, Adrian M.T.; Raven, Mark; Self, Peter
Graphical abstract: Highlights: Colour and crystallinity changes in heat-treated teeth can be measured using spectrophotometric and XRD analyses. Both analyses provide numerical data for colour and hydroxyapatite crystallite size. Results demonstrate crystal size and yellowness were significantly affected by the rise of heating temperature. The integration of both analyses can generate a reliable and accurate estimation of temperature exposure for burned dental remains. Abstract: Heat alters colour and crystallinity of teeth by destruction of the organic content and inducing hydroxyapatite crystal growth. The colour and crystallite changes can be quantified using spectrophotometric and x-ray diffraction analyses, however these analyses are not commonly used in combination to evaluate burned dental remains. In this study, thirty-nine teeth were incinerated at 300–1000 °C for 15 and 30 min and then measured using a spectrophotometer and an x-ray diffractometer. Response variables used were lightness, L*, and chromaticity a* and b* and luminance (whiteness and yellowness) for colour, and crystal size for crystallinity. Statistical analysis to determine the attribution of these variables revealed yellowness and crystal size were significantly affected by temperature ( p < 0.05), whilst duration of heat-exposure showed no significant effect. This study suggests the inclusion of both spectrophotometric and x-ray diffraction in investigating thermal-heated teeth is useful to accurately estimate the temperature teeth are exposed to.